Melt Quality induced Failure of Electrical Conductivity (EC) grade Aluminum Wires - Khaliq, Abdul; Rafiq, Muhammad Asif; Ali, Hafiz Tauqeer; Ahmad, Furqan; Mehmood, Shahid; Grandfield, John; Ranjha, Sagheer Abbas (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
The failure of electrical conductivity grade (EC) aluminum during wire drawing process was investigated. The fractured aluminum wires were subjected to scanning electron microscopic (SEM) and energy dispersive X-ray (EDX) analysis for initial examination. Thermodynamic analysis of molten aluminum interaction with refractories was also carried using FactSage at temperatures of 710oC to predict stable phases. The SEM analysis revealed the presence of 2nd phase particles as inclusions in the cracked openings either in the form of deformed elongated or debris of oxides. The possible types of inclusions identified with EDX were Al2O3, Al3C4 (Al-Carbide), refractory bricks elements (Al, Mg, Si and O). The microscopic analysis of the polished samples revealed that these inclusions were fine ranging from 0.1 µm to 30 µm in size. The presence of transition metal borides particles was not identified during SEM analysis which may be fine enough to be detected with this microscope. The overall investigation suggested that the possible cause of this failure is the presence of 2nd phase particles as inclusions in the aluminum matrix, and it was associated with the poor quality of melt. During wire drawing process, these inclusions were pulled out of aluminum matrix by the wire-drawing forces to produce micro-voids which led to ductile tearing and final fracture of wires. It was recommended to use ceramic foam filters to isolate inclusions from molten aluminum.